Multi-objective Collaborative Optimization of Steel Structure Central Support Components Integrating NSGA-II and Topology Optimization - Han, Lei; Zheng, Heng; Weng, Jianying; Li, Xue (Engineering Transactions, 2026)
This paper presents a multi-objective collaborative optimization framework for central support components in steel structures, aiming to simultaneously minimize structural mass and compliance. Traditional design methods often optimize a single objective, limiting overall performance. To address this, we integrate the NSGA-II genetic algorithm with the SIMP topology optimization method within a master-sub nested architecture. NSGA-II performs a global search for optimal macro-level geometric parameters, while SIMP optimizes the micro-level material distribution under given geometries. The interaction between both levels enables a comprehensive trade-off between lightweight design and structural stiffness. Case studies on various support types demonstrate that the proposed method effectively reduces structural mass while enhancing stiffness, confirming its robustness and broad applicability. The Pareto front achieves a high Hypervolume (HV) index, indicating excellent solution diversity and quality. This approach provides an intelligent and efficient pathway for the high-performance, lightweight design of steel structures.